2014
DOI: 10.1111/josh.12157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Food Service Nutrition Improvements on Elementary School Cafeteria Lunch Purchase Patterns

Abstract: Elementary school children purchased healthier lunches when healthier menu items were offered and when less healthy foods were eliminated from the menu. There was no significant decline in the number of students who purchased lunches as nutritional improvements were made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 22 publications
1
23
0
1
Order By: Relevance
“…Table presents the intensity evaluation of studies aiming to modify behavior across different nutrition categories. Interventions in each category were highly effective: fruit and vegetable (N = 33; effective N = 27, ineffective N = 4, unknown effectiveness N = 2), general healthy eating (N = 53; effective N = 41, ineffective N = 10, unknown effectiveness N = 2), single food or food group (N = 12; effective N = 8, ineffective N = 3, unknown effectiveness N = 1), and single nutrient (N = 7; effective N = 5, ineffective N = 1, unknown effectiveness N = 1). Comparing the frequency of effective studies in different categories showed that the mean frequency of interventions in the single food or food group category was significantly higher than for the general healthy eating category (ANOVA p = .04, Tukey's post hoc test p = .03).…”
Section: Resultsmentioning
confidence: 99%
“…Table presents the intensity evaluation of studies aiming to modify behavior across different nutrition categories. Interventions in each category were highly effective: fruit and vegetable (N = 33; effective N = 27, ineffective N = 4, unknown effectiveness N = 2), general healthy eating (N = 53; effective N = 41, ineffective N = 10, unknown effectiveness N = 2), single food or food group (N = 12; effective N = 8, ineffective N = 3, unknown effectiveness N = 1), and single nutrient (N = 7; effective N = 5, ineffective N = 1, unknown effectiveness N = 1). Comparing the frequency of effective studies in different categories showed that the mean frequency of interventions in the single food or food group category was significantly higher than for the general healthy eating category (ANOVA p = .04, Tukey's post hoc test p = .03).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, taste testing can predict student interest in nutrition education Engage food service staff and parents in training activities to reinforce the home and lunchroom environment, which will help sustain behaviors learned in class Finally, Cooperative Extension developed cross‐cultural, experiential learning approaches grounded in evidence‐based nutrition curriculum can supplement school curriculum and leverage community resources …”
Section: Implications For School Healthmentioning
confidence: 99%
“…Thus, it is imperative that the food we offer to our patients is healthful and that they are educated about positive food choices. In another study, Cluss et al (2014) found that elementary school children purchased healthier lunches when offered a healthier lunch menu and the less healthy items were removed from the menu.…”
Section: Review Of Literaturementioning
confidence: 98%
“…In another study, Cluss et al. () found that elementary school children purchased healthier lunches when offered a healthier lunch menu and the less healthy items were removed from the menu.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation